Sportomics: Futbol Club Barcelona's approach to personalized injury prevention - Rodas, G.; Gonzalez, J. R. (Apunts Sports Medicine, 2024)
Sportomics combines "omics" sciences with classic clinical laboratory analyses to mimic the real challenges and conditions faced during sports training and competition.1 It relies on analytical methods with high processing power to analyze large volumes of data and is a promising field of investigation in translational sports medicine. Sportomics comprehensively relies on the "athlete's biological passport" for the systematic study of sport-induced responses and adaptations at any level (genome, transcriptome, proteome, metabolome, etc.).2 The use of omics data provides a comprehensive understanding of the biological processes and systems underlying athletic performance and injury risk, to finally identify novel intervention targets.